Clumped‐Isotope Constraint on Upper‐Tropospheric Cooling During the Last Glacial Maximum. Issue 4 (17th August 2022) - Banerjee, Asmita; Yeung, Laurence Y.; Murray, Lee T.; Tie, Xin; Tierney, Jessica E.; Legrande, Allegra N.
Abstract: Ice cores and other paleotemperature proxies, together with general circulation models, have provided information on past surface temperatures and the atmosphere's composition in different climates. Little is known, however, about past temperatures at high altitudes, which play a crucial role in Earth's radiative energy budget. Paleoclimate records at high‐altitude sites are sparse, and the few that are available show poor agreement with climate model predictions. These disagreements could be due to insufficient spatial coverage, spatiotemporal biases, or model physics; new records that can mitigate or avoid these uncertainties are needed. Here, we constrain the change in upper‐tropospheric temperature at the global scale during the Last Glacial Maximum (LGM) using the clumped‐isotope composition of molecular oxygen trapped in polar ice cores. Aided by global three‐dimensional chemical transport modeling, we exploit the intrinsic temperature sensitivity of the clumped‐isotope composition of atmospheric oxygen to infer that the upper troposphere (effective mean altitude 10–11 km) was 6–9°C cooler during the LGM than during the late preindustrial Holocene. A complementary energy balance approach supports a minor or negligible steepening of atmospheric lapse rates during the LGM, which is consistent with a range of climate model simulations. Proxy‐model disagreements with other high‐altitude records may stem from inaccuracies in regional hydroclimate simulation, possibly related to land‐atmosphere feedbacks. Plain Language Summary: Atmospheric temperatures at high altitudes determine the fate of montane glaciers and the energy balance of the planet. They change with Earth's climate, but our knowledge of this relationship is poor: the few available temperature records for high‐altitude cooling at the most recent ice age, which are limited to the tropics, disagree with model predictions for unknown reasons. Here we report a global‐scale constraint for high‐altitude temperature, applied to the last ice age, which yields results consistent with global climate model predictions. This new proxy―based on the isotopic variants of molecular oxygen trapped in polar ice cores―can be applied deeper in the past to understand the relationship between surface and high‐altitude temperatures in different climates. Key Points: Measurements of O2 clumped isotopes in polar ice cores are compared to predictions from three‐dimensional chemical transport modeling Measured and modeled change in O2 clumped isotope values between the Last Glacial Maximum (LGM) and preindustrial agree within uncertainty Clumped‐isotope results imply a minor global lapse‐rate steepening at the LGM relative to the preindustrial